2018
DOI: 10.1007/978-3-319-92046-7_40
|View full text |Cite
|
Sign up to set email alerts
|

Human-Automation Teaming: Lessons Learned and Future Directions

Abstract: Full autonomy seems to be the goal for system developers in almost every area of the economy. However, as we move from automated systems to autonomous systems, designers have needed to insert humans to oversee automation that has traditionally been brittle or incomplete. This creates its own problems as the operator is usually out of the loop when the automation hands over problems that it cannot handle. To better handle these situations, it has been proposed that we develop human automation teams that have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Pilots expressed particularly high willingness to fly with DFAs in the setting of a single-pilot operation, which is similar to findings by Battiste et al [4]. Furthermore, the pilots highlighted that, to be successful, a DFA should be able not only to provide a practical support, but also to read the relational context of the cockpit.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Pilots expressed particularly high willingness to fly with DFAs in the setting of a single-pilot operation, which is similar to findings by Battiste et al [4]. Furthermore, the pilots highlighted that, to be successful, a DFA should be able not only to provide a practical support, but also to read the relational context of the cockpit.…”
Section: Discussionsupporting
confidence: 80%
“…Ethics approval was obtained from the university's human research ethics committee 4 . The study was classified as low risk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes other initial research approaches and current advances in automation. Various studies have already evaluated automation tools for RCO empirically concluding such operations including ground support are viable in near future (Battiste et al 2018;Lachter et al 2017;. Other proposals have validated advanced automation tools for MCO, which autonomously monitor and evaluate pilot health as well as hazardous of entries into aircraft (Çakır et al 2016;Gateau et al 2018;Gaultier and SAFEE Consortium 2008;Hanakova et al 2017;Laviv and Speijker 2007;Maiolo et al 2017;Oliveira et al 2012;Schmitt et al 2010).…”
Section: Cognitive Work Analysis (Cwa)mentioning
confidence: 99%
“…and through direct interactions with the onboard pilot. Based on these findings, Battiste et al (2018) suggested that the decision of how dedicated assistance should be provided could be left to air carriers based on their analyses of cost-benefit ratios.…”
Section: Ground-based Operational Conceptsmentioning
confidence: 99%